2007
DOI: 10.1113/jphysiol.2006.123919
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐type‐specific excitatory and inhibitory circuits involving primary afferents in the substantia gelatinosa of the rat spinal dorsal horn in vitro

Abstract: The substantia gelatinosa (SG) of the spinal dorsal horn shows significant morphological heterogeneity and receives primary afferent input predominantly from Aδ-and C-fibres. Despite numerous anatomical and physiological studies, correlation between morphology and functional connectivity, particularly in terms of inhibitory inputs, remains elusive. To compare excitatory and inhibitory synaptic inputs on individual SG neurones with morphology, we performed whole-cell recordings with Neurobiotin-filled-pipettes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
159
1
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(181 citation statements)
references
References 53 publications
(111 reference statements)
15
159
1
6
Order By: Relevance
“…Previous work indicates that most neurons located in lamina I of the spinal cord, being either excitatory or inhibitory, receive monosynaptic input from either A␦-fibers and/or C-fibers (Yoshimura and Jessell, 1990;Dahlhaus et al, 2005;Yasaka et al, 2007;Pinto et al, 2010), and many also express group I mGluRs (Alvarez et al, 2000). In the present study, we recorded from unidentified lamina I neurons and showed that LTP GABA could Figure 7.…”
Section: Potential Functional Consequences Of Ltp Gaba In Nociceptivesupporting
confidence: 48%
“…Previous work indicates that most neurons located in lamina I of the spinal cord, being either excitatory or inhibitory, receive monosynaptic input from either A␦-fibers and/or C-fibers (Yoshimura and Jessell, 1990;Dahlhaus et al, 2005;Yasaka et al, 2007;Pinto et al, 2010), and many also express group I mGluRs (Alvarez et al, 2000). In the present study, we recorded from unidentified lamina I neurons and showed that LTP GABA could Figure 7.…”
Section: Potential Functional Consequences Of Ltp Gaba In Nociceptivesupporting
confidence: 48%
“…This suggests that many inhibitory interneurons corelease GABA and glycine, whereas others release only GABA. However, electrophysiological studies have identified synapses in this region that are purely Gly (3,54,55). Although these may involve axons that originate from Gly neurons located outside laminae I-III, in many cases the lack of a GABAergic component prob ably results from the absence of GABAA receptors at these synapses (3).…”
Section: Figurementioning
confidence: 99%
“…Central cells receive excitatory inputs from C-afferents and primary-afferentevoked inhibitory inputs mediated by both Aδ-and C-fibres. The excitatory inputs to radial cells were mediated by both Aδ-and C-fibres (17). In addition, the lamina II central, and the radial cells, receive an intralaminar-derived inhibitory input from islet cells.…”
Section: Gabaergic Neuronal Circuit In Spinal Dorsal Hornmentioning
confidence: 98%
“…Islet cells and central cells were located in lamina Ili, IIo and near the border of laminae Ili and IIo. Their dendritic trees spread in the rostrocaudal direction (17). Somata of vertical neurons located in lamina IIo and pass ventrally through laminae II -IV.…”
Section: Gabaergic Neuronal Circuit In Spinal Dorsal Hornmentioning
confidence: 99%
See 1 more Smart Citation